Gambling for recovery? Exploring the riskiness of European insurers' assets during the Covid-19 crisis 2020 - Marcel Beyer (Goethe University Frankfurt, International Center for Insurance Regulation (ICIR), 2023)
In crisis times, insurance companies might feel the pressure to present a performance of their investment portfolios that is superior to the market, since investment portfolios back the claims of policyholders and serve as a signal for the claims' safety. I seek to show whether a stock market crisis as experienced over the course of the Covid-19 pandemic influences insurance firms' decisions on the allocation of credit risk bearing assets in their investment portfolio. I find, consistently with previous research, that insurers shift their portfolio holdings towards lower credit risk assets as financial market conditions tighten. This tendency seems to be restricted by the liquidity risk of high-yield assets, and the credit risk of lower-rated investment-grade assets. Both effects ultimately lead to a larger fraction of less liquid assets during the crisis and the recovery.
Keywords: G01; G11; G22; G32; 330; Insurance; Covid-19; Financial Stability